Policy Analysis of Gastrointestinal Cancer Prevention in Iran: A Framework Based on a Qualitative Study. Issue 3 (7th March 2021) - Kabiri, Neda; Khodayari‐zarnaq, Rahim; Khoshbaten, Manouchehr; Janati, Ali
Abstract : This study aimed to analyze the current policies of common gastrointestinal cancer prevention. This qualitative instrumental case study was conducted in 2019 to analyze policies using the "policy triangle framework." Two data collection methods were used: document review and semistructured interviews. The country's related documents were searched through databases. Semistructured interviews were conducted at the interviewee's workplace. In total, 22 participants were interviewed, 12 of whom were from the Ministry of Health. Interviews and documents were analyzed using directed content analysis in MAXQDA v10 software. Interobserver reliability, peer check, and member check were done to confirm the trustworthiness of data. The main contextual factors affecting gastrointestinal cancers in Iran were socioeconomic, structural, political, and legal factors. Content of gastrointestinal cancer prevention in the national policies were mostly about lifestyle changes, food security, and environmental conditions. Efforts for cancer prevention policymaking in Iran starts in 1984 with a top‐down approach to the implementation and three types of evaluation. Stakeholders of gastrointestinal cancer prevention policies in Iran were categorized into three groups of governmental, nongovernmental, and semigovernmental organizations. Coordination among different organizations should be strengthened through setting common goals and creating a shared vision, and finally, political leadership should be realized by the Ministry of Health.